Buying time: futures trading and telegraphy in nineteenth-century global commodity markets*. Issue 2 (19th June 2015) - Engel, Alexander
Abstract: Adapting the dictum that 'time is money', Western merchants have long promoted and welcomed technologies to accelerate commerce. Thanks to revolutionary changes in communication in the nineteenth century, including the telegraph, information could for the first time travel much faster around the globe than goods. This asymmetric time–space compression created new problems for agents of global trade, as transactions could occur faster than the handling of the goods. Yet this problem also presented an opportunity to establish new forms of trading and ways of thinking about time. In the case of world markets for primary products such as grain or cotton, the new technique of futures trading at commodity exchanges became a tool to redress the time differential between the movement of goods and information. It pushed the commercial community to think in a 'double time' of a dematerialized present and a material future with physical goods, and centred global commodity markets on a few marketplaces. The article thus argues that historians need to examine economic understandings of the future alongside political, cultural, and social understandings.